OPINI AUDIT DAN PERGANTIAN AUDITOR: KAJIAN BERDASARKAN RESIKO, KEMAMPUAN PERUSAHAAN DAN KINERJA AUDITOR - Srimindarti, Ceacilia (Fokus Ekonomi, 2006)
Today, the business word work under increasing stiff competition. In such an environment, public accountant or audit firm should seek to enhance their competitiveness so they will not switch by their client. This article explore auditor switching action. Propensity of client to change auditors affect auditor when expressing the audit opinion. There are many factors which influence client to change auditor. One of the faktor is regulation. However, other factors also have an inportant impact an auditor switch. The faktor are company size, company growth, bankruptcy, client business risk, audit opinion, audit delay and audit fee.Keywords : Auditor Opinion, Auditor Switch, Company Size, Company Growth, Bankruptcy, Business Risk, Audit Delay, Audit Fee.